Vaccination and GDP Growth Rates: Exploring the Links in a Conditional Convergence Framework. (March 2018) - Masia, Neal A.; Smerling, Jonathan; Kapfidze, Tendayi; Manning, Richard; Showalter, Mark
Highlights: An econometric model estimates how changes in immunization coverage impact GDP. Increases in vaccination estimated to boost GDP growth across countries and time. Reductions in immunization could slow down GDP growth over an extended period. Analysis shows substantial economic returns to a one-time coverage improvement. ROI results offer enhanced case for prioritizing vaccinations in healthcare budgets. Summary: Vaccination rates vary significantly across countries, and the intensity of vaccination programs is a matter of public choice, infrastructure limitations, budget constraints, and many other factors. The link between better health and better economic performance is by now well established, and many vaccines have been shown to generate significant ROI in a classical cost-benefit framework. To our knowledge, the longer term macroeconomic benefits of improved vaccination programs have not been estimated. We modify the standard conditional convergence model to account for changes in vaccination rates across time and countries, and use the modified model to estimate the macroeconomic gains from improved vaccination rates, using the DTP vaccine as a proxy for vaccination programs generally. We find evidence to suggest economically and statistically significant and sustained increases in the GDP growth rate associated with lagged increases in vaccination rates; furthermore, we find these effects increasing over time. We find that investments of the sort made by the Global Alliance for Vaccination and Immunization (Gavi) are linked to measurably higher DTP rates, and we estimate the returns to such investments as at least 12:1. For countries on the threshold of graduating from Gavi, these results suggest that much is at stake: reducing investment in vaccination could reverse both the public health improvements and tangible economic benefits associated with ongoing improvements in vaccination rates.